Use of indocyanine green near-infrared lymphography to detect sentinel lymph nodes in a dog with a malignant insulinoma: a case report - Nolff, Mirja Christine; Dennler, Renate; Dennler, Matthias (Frontiers in Veterinary Science, 2023)
Malignant insulinoma is the most frequent neuroendocrine tumor of the canine pancreas. Canine insulinoma display malignant behavior and high metastatic rates have been described. The most frequent site of metastases are the draining lymph nodes, which are also the prime location of recurrence of functional disease. However, identification of metastatic nodes is often complicated as the pancreas is drained by numerous lymphocenters, and clinical enlargement or structural changes are not always present in metastatic nodes. Unaltered nodes are frequently small (few mm) and hard to discern from surrounding tissue. Therefore, lymphadenectomy is recommended in affected dogs. In contrast to human medicine, there are currently no structured strategies for nodal resection available for dogs. This report describes a technique for sentinel node mapping of a malignant insulinoma in a dog. A total of 6 sentinel nodes were detected and resected using indocyanine green and Near infrared lymphography (NIRFL) during surgery. This technique could resemble a more structured approach for nodal resection in affected dogs- and potentially people- in the future. However, potential therapeutic benefits must be evaluated in a larger cohort of cases.